Role of delta-9-tetrahydrocannabinol in neurogenesis and neuronal plast - Sulaiman, Noor Azuin (2013)
Cannabis is classified as a halucinogen, is prepared as a bhang, ganja, hashish, and marijuana. Three putative varieties of cannabis are Cannabis sativa, Cannabis indica, and Cannabis ruberalis. Delta-9-tetrahydrocannabinol (Δ9-THC), also known as tetrahydrocannabinol, is the main psychoactive substance derived from Cannabis sp.. Δ9-THC is used in treating pain, asthma and coughs, also acts as sedative agent. It was known to show impairment effects on variety of central effects including producing hypothermia, antinociception and changes of locomotor activity, immediate recall, memory retrieval, and also in working and short-term memory. Δ9-THC was known to alter the neurogenesis and neuronal plasticity observed in animal models. However, the doses used in experiments were high and even higher in cell culture method. The purposes of this study was to observe the effects of Δ9-THC at lower dose on neurogenesis and neuronal plasticity involving nociception and cognitive performances in acute (7 days) and chronic (21 days) treatments on Spraque dawley rats. Three doses of Δ9-THC were used; 0.75, 1.5 and 3.0 mg/kg, and 0.9% normal saline with 3% ethanol was used as a control. Two types of behavioural tests were run; hot plate and novel-object discrimination (NOD) tests, for observing the nociception and cognitive performances, respectively. The brain samples were collected for further analyses with Western blot technique to determine the protein concentration of Doublecortin (DCX), c-fos, and downstream regulatory element modulator (DREAM) as a marker for cognitive and nociception, respectively. The brain was also inveigated using immunohistochemistry (IHC) technique, in detecting the BrdU, DCX, nestin, Class III β-tubulin (TuJ-1), and glial fibrillary acidic protein (GFAP) as markers for neurogenesis. Cresyl violet stain was used for observing the neuronal cell death (NCD) present in the hippocampus of the brain. Liver and kidney were collected and further processed with hematoxylin and eosin stain in observing the toxicity effects of Δ9-THC. 1.5 mg/kg of Δ9-THC gave significant differences at p < 0.001 when compared to control, 0.75, and 3.0 mg/kg of Δ9-THC observed on the neurogenesis, cognitive function and nociceptive response. The observations were acceptable for both acute and chronic treatments, behavioural and molecularly. Meanwhile, all dosages of Δ9-THC showed significant differences at p < 0.001 as compared to control on toxicity test involving brain after giving stress. In studying the effect on liver and kidney, all dosages of Δ9-THC and control showed no significant difference at p > 0.05. From these results, it can be concluded that 1.5 mg/kg of Δ9-THC improved the level of neurogenesis and neuronal plasticity when compared to control, 0.75 and 3.0 mg/kg of Δ9-THC. Δ9-THC at all dosages used was observed to give neuroprotective function against stress. Treatment of Δ9-THC showed no toxic effect observed in the kidney and liver.